2004
DOI: 10.1007/s00027-003-0647-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laurentian Fulvic Acid luminescence with that of the hydroquinone/quinone model system: Evidence from low temperature fluorescence studies and EPR spectroscopy

Abstract: Fluorescence techniques have been used to identify humic substances, (e.g. aquatic fulvic acids from different origins). Synchronous scans have proven adequate for distinguishing detail and differentiating samples. As well, fluorescence has often been used to probe humic interactions with metals and xenobiotic organics. In this study, the fluorescence of a well-characterized material, Laurentian fulvic acid (LFA) was compared with that of a simple hydroquinone/quinone (H 2 Q/Q) model system. Synchronous fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 11 publications
7
52
0
Order By: Relevance
“…The FIC3 component showed characteristics of tryptophan-like fluorescence and was similar to other previously reported PARAFAC components, which have been associated to tryptophan-like, protein-bound and free amino acids (Yamashita and Tanoue, 2003;Stedmon and Markager, 2005b;Murphy et al, 2008;Kothawala et al, 2012;Kowalczuk et al, 2013).The spectral characteristics of FIC4 have not been traditionally defined (Coble, 1996) but it occupies a region very close to those of the humiclike substances. Other studies that have found this component, mainly in the watershed of tropical rivers (Yamashita et al, 2010a) and its estuaries (Brym et al, 2014), have assigned it to a microbial reduced quinone-like substance (Ariese et al, 2004;Cory and McKnight, 2005).…”
Section: Parafac Component Source Identificationmentioning
confidence: 97%
“…The FIC3 component showed characteristics of tryptophan-like fluorescence and was similar to other previously reported PARAFAC components, which have been associated to tryptophan-like, protein-bound and free amino acids (Yamashita and Tanoue, 2003;Stedmon and Markager, 2005b;Murphy et al, 2008;Kothawala et al, 2012;Kowalczuk et al, 2013).The spectral characteristics of FIC4 have not been traditionally defined (Coble, 1996) but it occupies a region very close to those of the humiclike substances. Other studies that have found this component, mainly in the watershed of tropical rivers (Yamashita et al, 2010a) and its estuaries (Brym et al, 2014), have assigned it to a microbial reduced quinone-like substance (Ariese et al, 2004;Cory and McKnight, 2005).…”
Section: Parafac Component Source Identificationmentioning
confidence: 97%
“…[24][25][26] The basic feature of any quinhydrone complex is the stable face-to-face, donor-acceptor, and hydrogen-bonding interactions between a hydroquinone and quinone moiety. The most simple, classic example of a quinhydrone is the stable noncovalently interacting dimer complex formed by p-benzoquinone (cyclohexa-2,5-diene-1,4-dione) with 1,4-hydroquinone (benzene-1,4-diol) (Fig.…”
Section: Quinhydrone Supramolecular Complexesmentioning
confidence: 99%
“…This compact and stable complex can be synthesized as dark shining needles, with moderate water solubility, from a 1:1 mixing of the reactants. 26 Quinhydrone complexes will form spontaneously through self-assembly interactions on mixing (solution). A myriad of quinhydrones may synthesized by varying functionalities at the carbon centers (Fig.…”
Section: Quinhydrone Supramolecular Complexesmentioning
confidence: 99%
See 2 more Smart Citations